Urban Identity of Pula and Roman Pottery from St. Theodore’s Quarter 2005 - Starac, Alka (Rei Cretariae Romanae Fautorum Acta, 2015)
Rescue archaeological research has been carried out from 2005 to 2009 in St. Theodore’s quarter, an area of 4000 square metres situated in the northeast corner of the urban nucleus of Pula. The locality has been settled continuously for 3000 years and seven principal building phases were detected. The oldest remains of habitations are dated to the 10th century BC, to the beginning of the Histrian Iron Age. Roman architectural remains are dated to the second half of the 1st century BC and cover almost the whole excavated area. They include a sanctuary of Hercules, public thermae, a luxuriously equipped domus, an aqueduct and carefully planned canalisation and drainage systems. Following the destruction of the Roman sanctuary, thermae and domus in a fire towards the end of the 5th century AD, an early Christian church probably dedicated to St. Lucy was built on the ruins of the baths, in the same time as attached facilities for the production of olive oil.